From Sangbo to urban landscape: morphological and hydrological transformations of Xuanwu Lake through integrating historical interpretation and geographic analysis - Wang, Xueyuan; Cheng, Yuning (Frontiers in Environmental Science, 2024)
Xuanwu Lake in Nanjing has undergone a rich history, evolving from native Sangbo to a naval training ground, from an imperial garden to farmland, and finally to a vibrant urban landscape. The lake's legacy can be attributed to its unique geographical and hydrological conditions. Exploring historical transformations of the lake and surrounding landscape patterns provides insights for optimizing urban-water space relationship in contemporary China. Traditional analyses of lake changes based solely on historical records may lack precision due to deviations and artistic interpretations found in ancient maps. However, considering the reciprocal compatibility between local geomorphology, undulating terrains, and water bodies allows for accurate reduction of the lake's morphology by inferring and validating its geographical features. This research combines historical interpretation and geographical analysis to reconstruct the historical shape of Xuanwu Lake, uncover the intrinsic mechanisms driving spatial changes over time, and analyze the morphological changes and connectivity patterns of its hydrological system. The morphology and hydrological dynamics of Xuanwu Lake are deeply intertwined with the policies prevailing in different eras. In antiquity, Xuanwu Lake, as a natural body of water, sustained the surrounding ecosystem and the livelihoods of local inhabitants. During the imperial period, it was integrated into the royal gardens, with its utilization and configuration modified by political directives, including the establishment of a naval training facility and its conversion into a royal recreational venue. Subsequently, in response to economic imperatives, Xuanwu Lake was transformed into agricultural land, which led to challenges such as flooding and drought. Ultimately, due to urbanization pressures, it was restored to lake form. By interpreting the bidirectional adaptation between the lake's ecosystem functions and city development activities, this research provides insights for water space management and ecological restoration in contemporary Xuanwu Lake. The findings provide guidance for the sustainable development of city-water relationships to enhance the resilience of urban ecological spaces.